Five-Fold Variation Among Surgeons and Hospitals in the Use of Secondary Palate Surgery. (May 2019) - Sitzman, Thomas J.; Carle, Adam C.; Heaton, Pamela C.; Helmrath, Michael A.; Britto, Maria T.
Objective: To identify child-, surgeon- and hospital-specific factors at the time of primary cleft palate repair that are associated with the use of secondary palate surgery. Design: Retrospective cohort study. Setting: Forty-nine pediatric hospitals. Participants: Children who underwent cleft palate repair between 1998 and 2015. Main Outcome Measure: Time from primary cleft palate repair to secondary palate surgery. Results: By 5 years after the primary palate repair, 27.5% of children had undergone secondary palate surgery. In multivariable analysis, cleft type and age at primary palate repair were both associated with secondary surgery ( P < .01). Children with unilateral cleft lip and palate had a 1.69-fold increased hazard of secondary surgery (95% confidence interval [CI]: 1.54-1.85) compared to children with cleft palate alone. Primary palate repair before 9 months had a 3.99-fold increased hazard of secondary surgery (95% CI: 3.39-4.07) compared to repair at 16 to 24 months of age. After adjusting for cleft type, age at repair, and procedure volume, there remained substantial variation in secondary surgery use among surgeons and hospitals ( P < .01). For children with isolated cleft palate, the predicted proportion of children undergoing secondary surgery within 5 years of primary repair ranged from 8.5% to 46.0% across surgeons and 9.1% to 49.4% across hospitals. Conclusions: There are substantial differences among surgeons and hospitals in the rates of secondary palate surgery. Further work is needed to identify causes for this variation among providers and develop interventions to reduce the need for secondary surgery.